1998
DOI: 10.1002/(sici)1097-4601(1998)30:12<913::aid-kin6>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Absolute rate constants for F + CH3CHO and CH3CO + O2, relative rate study of CH3CO + NO, and the product distribution of the F + CH3CHO reaction

Abstract: Using a pulse-radiolysis transient UV-VIS absorption system, rate constants for the reactions of F atoms with CH 3 CHO (1) and CH 3 CO radicals with O 2 (2) and NO (3) at 295 K and 1000 mbar total pressure of SF 6 was determined to be Ϫ10 k ϭ (1.4 Ϯ 0.2) ϫ 10 , k ϭ 1 2 By monitoring the for-Ϫ12 Ϫ11 3 Ϫ1 Ϫ1(4.4 Ϯ 0.7) ϫ 10 , and k ϭ (2.4 Ϯ 0.7) ϫ 10 cm molecule s . 3 mation of CH 3 C(O)O 2 radicals ( Ͼ 250nm) and NO 2 ( ϭ 400.5nm) following radiolysis of SF 6 /CH 3 CHO/O 2 and SF 6 /CH 3 CHO/O 2 /NO mixtures, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…We have been unsuccessful in finding a CH 3 CO source that does not involve acetaldehyde and yet is suitable for the purpose of DF kinetic studies. The experimental 15,16,27,28 and theoretical 29 rate constants reported for the overall reaction CH 3 CO + O 2 (1) are in accordance with each other, and they appear to define a sigmoidal-type k 1 vs. P pressure-dependence curve. In the low-pressure region (1.3-5 mbar He), McDade et al have determined k 1 (298 K) = (2.0 AE 0.4) Â 10 À12 cm 3 molecule À1 s À1 by using the flash photolysis technique with direct monitoring of CH 3 CO by photoionisation mass spectrometry.…”
Section: Kinetics Of the Overall Reaction Of Ch 3 Co With Osupporting
confidence: 75%
See 1 more Smart Citation
“…We have been unsuccessful in finding a CH 3 CO source that does not involve acetaldehyde and yet is suitable for the purpose of DF kinetic studies. The experimental 15,16,27,28 and theoretical 29 rate constants reported for the overall reaction CH 3 CO + O 2 (1) are in accordance with each other, and they appear to define a sigmoidal-type k 1 vs. P pressure-dependence curve. In the low-pressure region (1.3-5 mbar He), McDade et al have determined k 1 (298 K) = (2.0 AE 0.4) Â 10 À12 cm 3 molecule À1 s À1 by using the flash photolysis technique with direct monitoring of CH 3 CO by photoionisation mass spectrometry.…”
Section: Kinetics Of the Overall Reaction Of Ch 3 Co With Osupporting
confidence: 75%
“…The parameter estimations have returned rate constants for the overall reaction CH 3 CO + O 2 (1) in good agreement with data reported from other laboratories. 15,27,28 The fitting procedures have also provided OH yields as a function of pressure. Since no absolute OH concentrations were measured in the experiments by Blitz et al, the yields they report are relative values and are given normalised to the lowest-pressure OH yield in their paper.…”
Section: Oh Yield For the Reaction Of Ch 3 C(o) With Omentioning
confidence: 99%
“…However, based on MC-TST calculations incorporating all conformers, we found that thermal decomposition of the tri-HPACYL-I acyl radicals is still sufficiently fast to dominate over O 2 addition; i.e. even when assuming a Boltzmann energy distribution, the predicted rate coefficient of ∼ 2 × 10 8 s −1 at 300 K (see Table 3) is significantly higher than the effective O 2 addition rate for acyl radicals, experimentally measured at ≤∼ 3 × 10 7 s −1 in atmospheric conditions (Sehested et al, 1998;Blitz et al, 2002;Park et al, 2004; Baulch et al, 2005;Atkinson et al, 2006;Carr et al, 2011). One could counter that the presence of -OOH groups might stabilize the acylperoxy radicals formed in the O 2 addition (e.g.…”
Section: Elimination Of Co From Tri-hydroperoxy Acyl Radicalsmentioning
confidence: 68%
“…In addition, the submodel MEGAN (Model of Emissions of Gases and Aerosols from Nature) was used to simulate biogenic emissions of tracers, including isoprene (Guenther et al, 2006). Global isoprene emissions were scaled to 595 Tg yr −1 , which is the best estimate by Sindelarova et al (2014). The model was run for 1.5 years (summer 2011-2012), during which the first half-year was used as spin-up and 2012 was used for analysis.…”
Section: Global Modelmentioning
confidence: 99%
“…However, based on MC-TST calculations, incorporating all conformers, we found that thermal decomposition of the tri-HPACYL-I acyl radicals is still sufficiently fast to dominate over O 2 addition, i.e. even when assuming a Boltzmann energy distribution, the predicted rate coefficient of ~210 8 s -1 at 300 K (see Table 3), is significantly higher than the effective O 2 -addition rate for acyl radicals, experimentally measured at  ~310 7 s -1 in atmospheric conditions (Sehested et al, 1998;Blitz et al, 2002;Park et al, 2004;Baulch et al, 2005;Atkinson 285 et al, 2006;Carr et al, 2011). One could counter that the presence of -OOH groups might stabilize the acylperoxy radicals formed in the O 2 addition (e.g.…”
Section: Elimination Of Co From Tri-hydroperoxy Acyl Radicalsmentioning
confidence: 70%